2001
DOI: 10.1074/jbc.m108696200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sequences within the γ-Carboxylase That Represent a Novel Contact Site with Vitamin K-dependent Proteins and That Are Required for Activity

Abstract: The vitamin K-dependent (VKD) carboxylase converts clusters of Glu residues to ␥-carboxylated Glu residues (Glas) in VKD proteins, which is required for their activity. VKD precursors are targeted to the carboxylase by their carboxylase recognition site, which in most cases is a propeptide. We have identified a second tethering site for carboxylase and VKD proteins that is required for carboxylase activity, called the vitamin K The vitamin K-dependent (VKD) 1 or ␥-carboxylase converts Glus to ␥-carboxylated Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 53 publications
0
18
2
Order By: Relevance
“…In contrast to their results, however, we found that C288S had only 56% activity, while they reported that this mutation had no effect on activity. Another discrepancy with their result is that we found that C343S had normal activity, while they found that its activity was significantly reduced compared with wild-type enzyme (35); all the other mutants were fully active.…”
Section: Identification Of Nem-modified Cysteine Residues Of the Carbcontrasting
confidence: 96%
See 1 more Smart Citation
“…In contrast to their results, however, we found that C288S had only 56% activity, while they reported that this mutation had no effect on activity. Another discrepancy with their result is that we found that C343S had normal activity, while they found that its activity was significantly reduced compared with wild-type enzyme (35); all the other mutants were fully active.…”
Section: Identification Of Nem-modified Cysteine Residues Of the Carbcontrasting
confidence: 96%
“…Because our results on the activity of carboxylase with point mutations C343S and C288S differ from those of Pudota et al (21,35), we isolated the virus DNA from which these mutant proteins were prepared and the entire cDNA sequence was again confirmed. Carboxylase Activity Assays-The carboxylase activity assay was performed in a total volume of 125 l containing 25 mM MOPS, pH 7.5, 500 mM NaCl, 0.8 M (NH 4 ) 2 SO 4 , 0.12% PC, 0.28% CHAPS, 4 M proFIX, 5 Ci of NaH 14 CO 3 (specific activity, 54 mCi/mmol), 222 M vitamin K hydroquinone, and 1.25 mM FLEEL.…”
Section: Methodsmentioning
confidence: 64%
“…The Arg325Glu variant is located within a domain of the GGCX gene that mediates enzyme/substrate interactions [45]. Our study also failed to support a substantial role for allelic variants in the APOE gene as determinants of AC/PC maintenance doses, as has been suggested previously.…”
Section: Discussioncontrasting
confidence: 72%
“…Mutation to Ser was chosen because Ser is the most conservative substitution and therefore less likely to destabilize protein structure, which could confound analysis, and because Ser substitution for the Cys catalytic bases can result in large decreases in activity (24)(25)(26)(27)(28). We previously generated several of these mutants [C99S, C139S, C288S, C311S, C343S, and C450S (23,30)], and the remainder were generated in these studies (Supporting Materials and Methods). The specific activities were determined by carboxylase assay and quantitative Western analysis of microsomes.…”
Section: Mutants With Individual Cys To Ser Substitutions Retain Carbmentioning
confidence: 99%
“…Cys-343 lies within a region of the carboxylase that binds VKD proteins (30), and substitution by Ser caused partial loss of activity (Table 3). However, the same specific activity was observed when Cys-343 was substituted by a nonionizable Ala, ruling out the possibility of this Cys serving as the catalytic base.…”
Section: Mutants With Individual Cys To Ser Substitutions Retain Carbmentioning
confidence: 99%